Ultra-Deep Massive Parallel Sequencing of Plasma Cell-Free DNA Enables Large-Scale Profiling of Driver Mutations in Vietnamese Patients With Advanced Non-Small Cell Lung Cancer - Tran, Le Son; Nguyen, Quynh-Tho Thi; Nguyen, Chu Van; Tran, Vu-Uyen; Nguyen, Thai-Hoa Thi; Le, Ha Thu; Nguyen, Mai-Lan Thi; Le, Vu Thuong; Pham, Lam-Son; Vo, Binh Thanh; Dang, Anh-Thu Huynh; Nguyen, Luan Thanh; et al. (Frontiers in Oncology, 2020)
Population-specific profiling of mutations in cancer genes is of critical importance for the understanding of cancer biology in general as well as the establishment of optimal diagnostics and treatment guidelines for that particular population. Although genetic analysis of tumor tissue is often used to detect mutations in cancer genes, the invasiveness and limited accessibility hinders its application in large-scale population studies. Here, we used ultra-deep massive parallel sequencing of plasma cell free DNA (cfDNA) to identify the mutation profiles of 265 Vietnamese patients with advanced non small cell lung cancer (NSCLC). Compared to a cohort of advanced NSCLC patients characterised by sequencing of tissue samples, cfDNA genomic testing, despite lower mutation detection rates, was able to detect major mutations in tested driver genes that reflected similar mutation composition and distribution pattern, as well as major associations between mutation prevalence and clinical features. In conclusion, ultra-deep sequencing of plasma cfDNA represents an alternative approach for population-wide genetic profiling of cancer genes where recruitment of patients is limited to the accessibility of tumor tissue site.